1977
DOI: 10.1103/physrevb.15.897
|View full text |Cite
|
Sign up to set email alerts
|

Surface-structure determination of the layered compounds MoS2and NbSe2

Abstract: The stacking sequence and interplane and interlayer separation of 2H-MoS2 and 28-NbSe2 are determined by the dynamical low-energy-electron diffraction approach. Although lateral reconstructions corresponding to alteration in the bulk stacking sequence at the surface are physically reasonable, we find that such reconstructions do not in fact occur for these two compounds. 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…Our result shows that when z is allowed to increase by ~2% compared to its bulk value (z=1.586Å) [31], the calculated bands agree surprisingly closely with the experimental measurements [19], even though our calculation does not capture many of the detailed physics of our crystal, such as spin-orbit coupling [25]. Note that our suggested increase in z is in contrast to a low-energy-electron-diffraction study of the top layer of single-crystal bulk MoS 2 , which reported a ~5% decrease of z within the topmost layer [32]. We again note that our deduction of an expansion of the out-of-plane lattice constant is driven simply by a desire to seek better agreement of the DFT-derived bands with measurements and is not a definitive finding.…”
Section: Introductioncontrasting
confidence: 52%
“…Our result shows that when z is allowed to increase by ~2% compared to its bulk value (z=1.586Å) [31], the calculated bands agree surprisingly closely with the experimental measurements [19], even though our calculation does not capture many of the detailed physics of our crystal, such as spin-orbit coupling [25]. Note that our suggested increase in z is in contrast to a low-energy-electron-diffraction study of the top layer of single-crystal bulk MoS 2 , which reported a ~5% decrease of z within the topmost layer [32]. We again note that our deduction of an expansion of the out-of-plane lattice constant is driven simply by a desire to seek better agreement of the DFT-derived bands with measurements and is not a definitive finding.…”
Section: Introductioncontrasting
confidence: 52%
“…interlayer spacing contractions found in the NbSe2 system, the shifts for MgC12 are comparable to the relaxations seen in the MoS2 surface, a S-MO interlayer spacing contraction of 4.7% and a S-S contraction of 3.0% [81]. In addition, expansions of the interlayer spacings, as seen in MgC12, are not unusual in the transition metal dichalcogenides; for example the TiSe2 surface has an intratrilayer expansion of 3.0% coupled with an intertrilayer spacing contraction of 1.0% [82].…”
Section: Discussionsupporting
confidence: 74%
“…32) to ∼1m 0 . [33][34][35] In the absence of a definitive estimate of m eff , we checked the dependence of the induced charge distribution on m eff by performing a Thomas-Fermilike calculation using a similar model for the screening of a MoS 2 multilayer as in Ref. 36.…”
Section: Superconducting Phase and Open Questionsmentioning
confidence: 99%